Inter-Organisational IT Governance: A Case Study of Municipal ICT Cooperation - Helin, Ari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2020)
ABSTRACT Changes in society and organisations’ business environments have increased the useof operating models, which favour inter-organisational cooperation and networking. The evolution of operating models also has a significant impact on organisations’ IT departments and ICT activities. Inter-organisational ICT cooperation and networking offer excellent opportunities to public organisations to develop and improve their operations. This study clarifies how public organisations in Finland have implemented interorganisational ICT cooperation. Especially the inter-organisational ICT cooperation between Finnish municipalities has been the target of the current study. The study clarifies why municipalities plan ICT cooperation and how they have implemented it. The study also reviews the benefits that municipalities have received or are seeking to obtain through ICT cooperation. In addition, the study clarifies how intermunicipal IT governance has been implemented and investigates the applicability of currently used theories explaining intra-organisational IT governance to describe inter- organisational IT governance. The study examines various inter-municipal ICT cooperation groups in Finland. The study reveals that even though municipality groups use many types of ICT cooperation, joint IT governance model-based decisions and clear goals often shine in their absence. The dominant form of collaboration in inter-municipal ICT cooperation is voluntary cooperation without any joint IT governance. The study reveals that without a joint IT governance, municipalities lose much of the benefits they could achieve through a joint IT governance model. The study also confirms the applicability of currently used theories describing the intra-organisational IT governance to describe inter-organisational IT governance. KEYWORDS: information technology, IT, IT governance, ITG, information and communication technology, ICT, inter-organisational, public organisations, municipal, ICT cooperation

TIIVISTELMÄ Muutokset yhteiskunnassa ja organisaatioiden toimintaympäristöissä ovat lisänneet sellaisten toimintamallien käyttöä, jotka suosivat organisaatioiden yhteistyötä ja verkottumista. Näillä muutoksilla on myös voimakas vaikutus organisaatioiden ITosastoihin ja ICT-toimintoihin. Uudenlaiset yhteistyön toimintamallit ovat luoneet tarpeen myös eri organisaatioiden yhteiselle IT-hallinnolle. Myös julkishallinnon organisaatioille tällainen yhteistyö tarjoaa hyvät mahdollisuudet kehittää ja tehostaa toimintaansa. Tässä tutkimuksessa selvitetään, kuinka Suomen julkishallinnossa toteutetaan organisaatioiden välistä ICT-yhteistyötä. Tutkimuskohteena on erityisesti kuntien välinen ICT-yhteistyö. Tutkimuksessa selvitetään, miksi kunnat suunnittelevat ICTyhteistyötä, miten ne toteuttavat sitä sekä miten tätä yhteistyötä hallitaan. Tutkimuksessa tarkastellaan myös niitä hyötyjä, joita kunnat ovat ICT-yhteistyön avulla saaneet tai pyrkineet saamaan. Lisäksi selvitetään, voidaanko nykyisin käytössä olevia, organisaatioiden sisäistä IT-hallintoa kuvaavia teorioita käyttää kuvaamaan organisaatioiden välistä IT-hallintoa. Tutkimuksessa on kartoitettu suomalaisten kuntien välisiä ICT-yhteistyöryhmiä. Tutkimuksessa selviää, että vaikka kuntaryhmät tekevät monenlaista ICTyhteistyötä, niin yhteiseen IT-hallintomalliin perustuvat päätökset ja yhteiset, selkeät tavoitteet loistavat usein poissaolollaan. Kuntien välisessä ICT-yhteistyössä hallitseva yhteistyömalli on vapaaehtoinen yhteistyö ilman yhteistä IT-hallintomallia. Tutkimuksen perusteella voi todeta, että kunnat menettävät suuren osan niistä hyödyistä, jotka ne voisivat saavuttaa yhteisen IT-hallintomallin avulla. Tutkimus vahvistaa nykyisin käytössä olevien, organisaatioiden sisäistä IThallintoa kuvaavien teorioiden käyttökelpoisuuden kuvaamaan organisaatioiden välistä IT-hallintoa. ASIASANAT: tietotekniikka, IT, IT-hallinto, tieto- ja viestintätekniikka, ICT, organisaatioiden välinen, julkinen sektori, kunta, ICT-yhteistyö